Myasthenia Gravis and Neuromyelitis Optica Association - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Investigators at the University of Oxford, UK and 8 other international neurology centers describe the clinical, serological, and temporal associations of myasthenia gravis (MG) and neuromyelitis optica spectrum disorder (NMOSD) in 16 patients.